A Comparative Study of Postal Mail Services and Courier Services with Special Reference to Kanniyakumari District (International Journal of Food and Nutritional Sciences, 2022)
In India, the media transmission industry shapes a fundamental aspect of the nation's monetary turn of events, with homegrown and unfamiliar organizations being critical institutional financial specialists in this division. As of late, the media transmission segment, other assistance segments, developed quickly in monetary significance after the rise of Courier benefits because of the way that individuals in varying backgrounds paying little heed to their pay levels have begun utilizing Courier administration. Accordingly a sound help market, which centers on all needs and needs of clients, is basic for the general development of media transmission part so as to animate monetary development of our nation. In India, there are numerous homegrown and unfamiliar claimed organizations under media transmission division, which prevalently center on giving Courier administration to the individuals. Along with mechanical turn of events, change of significant worth and globalization, the requests from the clients drive the need to change and build up an association by rapidly adjusting innovation to items or administration in a productive way to get points of interest of the Courier Service and India Post to showcase and fulfill the recipients (clients) with creative mechanical based administration. Hence there is a requirement for investigation of the Courier specialist co-ops and India Post to outline suitable systems to augment their client based assistance and fulfillment. In this study, the researcher would like to comparative study of postal mail services and courier services in Kanniyakumari District. The primary aim of this study is to understand the Demographic factors and satisfaction level of both services. For that the researcher circulate 120 samples circulated for both services in the study area and researcher used percentage, Garret ranking method and f-test used for analysis the collected data.